Environmental gradients and micro‐heterogeneity shape fine‐scale plant community assembly on coastal dunes. (18th May 2017) - Conti, Luisa; de Bello, Francesco; Lepš, Jan; Acosta, Alicia Teresa Rosario; Carboni, Marta
Abstract: Questions: How do fine scale community assembly processes (e.g., environmental filtering, symmetric competition, hierarchical competition, facilitation) vary along a natural stress gradient on coastal sand dunes? How does local environmental heterogeneity affect these processes? Location: Mediterranean coastal sand dunes, central Italy (Montalto Marina, Lazio region). Methods: We quantified spatial (co‐occurrence) and functional patterns (degree of divergence in the traits of co‐occurring species) at a fine scale (0.5 m × 0.5 m subplots) in herbaceous communities (2 m × 2 m plots) of coastal habitats along the sea–inland vegetation zonation. We then studied how the fine‐scale co‐occurrence patterns (aggregation vs segregation) varied across habitats of the zonation. Finally, we fitted linear models assessing the relationship of the fine‐scale functional patterns (convergence vs divergence) with (1) the average environmental conditions along the sea–inland environmental stress gradient, and (2) the environmental heterogeneity within plots. Results: Spatial and functional patterns conveyed complementary information. Within‐community spatial segregation was more common further from the sea, which suggests the dominance of competitive processes in the least stressed communities. Fine‐scale convergence or divergence depended, for all functional traits, on the average environmental conditions of the community along the gradient, suggesting an effect of environmental stress on the prevailing assembly processes. However, it also depended on the environmental heterogeneity within the community, suggesting that micro‐abiotic filtering might play a more important role than previously anticipated in determining fine‐scale community assembly. Conclusions: Our results suggest that contrasting assembly processes act simultaneously on community assembly along environmental gradients, both as a function of average environmental conditions and of local heterogeneity. Future studies assessing community assembly should therefore avoid neglecting the role of micro‐abiotic filtering in shaping functional patterns. Moreover, only by integrating multiple sources of information (trait patterns, spatial patterns and environmental variation) were we able to disentangle fine‐scale community assembly processes and reinforce our interpretation of community patterns. Abstract : Integrating trait patterns, spatial patterns, and environmental heterogeneity, allowed us to disentangle the different fine scale community assembly processes along a natural stress gradient. In coastal sand dunes communities, contrasting assembly processes act simultaneously along the stress gradient and as a function of local environmental heterogeneity. We highlight that micro‐environmental filtering might play a more important role than previously anticipated.